ANALISIS PROSEDUR PENGENAAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN PADA BADAN PENDAPATAN DAERAH KABUPATEN ENDE - Purwanto, Agus; Banda, Falentina Lucia; Kapa, Sesilianus (Jurnal Riset Ilmu Akuntansi, 2020)
BPHTB tax has officially become a regional tax with effect starting January 1, 2011. Thus, as of January 1, 2011 the Primary Tax Office (KPP Pratama) is no longer serving BPHTB service management, so taxpayers who will report BPHTB payments in connection with the property transaction process which is carried out will be directly hansled by the local Regency/City Government. In implementing the imposition, payment, collection and reporting procedures for the payment of Taxes for Acquisition of Rights on Land and Buildings (BPHTB) has not yet been implemented in accordance with applicable regulations both in the procedure and use of the system in the implementation of tax collection on Land and Building Acquisition Fees (BPHTB) so that the achievement in tax revenue for the acquisition of land and building rights (BPHTB) has not been maximal. The location of this research is the Regional Revenue Agency of Ende Regency. The data in this study were collected through documentation techniques regarding Ende Regency Regulation Number 2 of 2011 concerning Regional Taxes, Regent Regulation Number 20 of 2011 concerning Systems and Procedures for Acquisition of Land and Building Rights Acquisition Fees. Based on the results of the above research, there are obstacles that occur in implementing BPHTP procedures, among others, there are taxpayers who report their taxation activities dishonestly. For example, there is counterfeiting of receipts that allows BPHTB to be paid to be smaller than it should be and the Taxpayer Awareness Level is that there are still many tacpayers who are not honets or do not know the new rules that have been in effect since BPTHB has been transferred to become regional taxes. Like paying taxes. Taxpayers pay taxed based on NJOP (Sales Value of Tax Objects) which should be based on the agreed transaction price or based on the Tax Object Acquisition Value (NPOP). So that the efforts that must be made by the Ende Regency Regional Revenue Agency are to improve the performance of employees at the Ende Regency Regional Revenue Service so that the implementation of tax revenue and tax data can be directed according to applicable regulations.